Anselm's Quiet Radicalism*. Issue 1 (2nd January 2016) - Williams, Thomas
Abstract : It is characteristic of Anselm to adopt the formulations of his authorities while giving them meanings of his own, hiding conceptual disagreement by means of verbal echoes. Anselm's considerable originality sometimes goes unnoticed because readers see the standard Augustinian language and miss the fact that Anselm uses it to state un-Augustinian views. One striking instance of Anselm's quiet radicalism is his understanding of free choice and the fall. He seems to uphold standard Augustinian privation theory when he affirms that injustice is merely an absence of justice where justice should be; he seems also to be committed to the standard Augustinian view that everything that has being is created by God. A closer examination, however, shows that Anselm clearly has qualms about whether privation theory can do all of the work to which Augustine had tried to put it; and Anselm actually affirms that every free choice has being and yet is not created by God. I begin by showing that Anselm regards unjust acts as being ontologically on a par with just acts. Injustice itself is nothing, a privation; but an unjust volition is something, and indeed no less something than a just volition. Moreover, creatures have their volitions solely from themselves, not from God. So Anselm must deny that God is the creator of everything that has being: free choices have being, and creatures are the sole causes of those choices. Anselm explicitly draws this radical conclusion, but he does so quietly, without fanfare, taking care to provide ways in which he can still say all the traditional things but mean something radical.